Verkehrliche Maßnahmen für die Expo 2010 Shanghai. - Zhang, Ying (Deutscher Verkehrs-Verl., 2009)
Die Expo 2010 Shanghai steht unter dem Motto "Better City, Better Life". Die Gestaltung des Geländes soll eine richtungsweisende harmonische Stadtentwicklung darstellen, über sechs Monate lang von Mai bis Oktober 2010 mit einer Zukunftswirkung von mindestens 60 Jahren, wie es die Stadtregierung Shanghai proklamiert hat. Dabei ist die umweltfreundliche Verkehrsabwicklung von besonderer Bedeutung. Erklärtes Ziel der Verkehrsplanung für die Expo 2010 Shanghai ist daher ein modernes integriertes Gesamtverkehrssystem.

The vast area that makes up Shanghai - similar to other comparable mega cities - is faced with ongoing and steadily increasing traffic-related problems, in spite of lavish transport projects such as urban motorways and underground railways. The Expo area is located adjacent to the inner city (at a distance of only 4 km), and already has a relatively well developed transport infrastructure in place that has been undergoing - and continues to undergo - target-specific improvements. The world's biggest exhibition so far - with 240 nations intending to be present - is expected to welcome 70 to 80 million visitors, of whom 95 % will be from China proper. The transport-related measures are aimed at reducing the use of private cars to a minimum. The Expo area is traversed by four underground lines accessible via seven stations. Express buses will provide links with the airport and major hotels, while the 'park & ride' travel mode is also planned to be available. The secondary road system consists of two circular and ten radial roads. Since the Huangpu River crosses the Expo area, a special 'water bus' service will be provided along the river's bank. The integrated public transport system has been conceived to handle 52 per cent of visitors to the Expo. Measures of a non-technical nature will, for the duration of the exposition, be adopted in the form of staggered working hours within the city limits. Machines will be installed to cancel Expo entry tickets at all the main public transport interchange stations, in order to avoid bottlenecks at entrances to the exposition.
Transport-related measures for Expo 2010 in Shanghai.
Keywords: Verkehr; Personennahverkehr; ÖPNV; Verkehrsplanung; Verkehrssystem; Verkehrsnachfrage; Freizeitverkehr; Besucher; Ausstellung; Bauausstellung; Verkehrsaufkommen; Erschließung; Verkehrsregelung; Parken; Nachhaltigkeit; Großveranstaltung; Verkehrsüberwachung